The Root Length Of Mandibular Second Molar By Using Periapical Radiography On Batak Ethnics Aged 18-22 Years In Faculty Of Dentistry University Of Sumatera Utara - Kartika, Dewi; Putri, Rizky Agustin (IIUM Medical Journal Malaysia, 2017)
Introduction: Mandibular second molar teeth often undergoes dental problem. The root length of mandibular second molar should be known to assist in determining treatment of endodontic plan. However the length of root of each individual varies, therefore the purpose of this study was to determine the average of the root length of mandibular second molar on Batak ethnics by using periapical radiography. Periapical radiography is the most accurate method to evaluate the root length of mandibular second molar. Materials and Methods: The method of this research was descriptive with cross sectional approach. The number of samples were 50 students selected by purposive sampling and the data were collected by questionnaire and x-ray photographs. The research was conducted in Radiology Dental of Hospital, Faculty of Dentistry,University of Sumatera Utara, on March and April 2016. Results: The root length of mandibular second molar on Batak ethnic student in Faculty of Dentistry University of Sumatera Utara was 9-18 mm. Conclusion(s): It can be concluded that average of the root length of mandibular second molar for the mesial is 13.9 mm and at distal root is 12.4 mm.